Pengaruh Penambahan Kunyit (Curcuma domestica Val.) dan Lama Fermentasi Terhadap Karakteristik Mikrobiologis Urutan (Sosis Bali Terfermentasi) - Nyoman Semadi Antara; IdaBagus Wayan Gunam; A.A.Made Dewi Anggreni (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2015)
The aim of the research was to find out the effect of turmeric used in the urutan formulationon the microbiological characteristic of urutan. In production of urutan, two strains of lactic acidbacteria (LAB), Lactobacillus plantarum U201 and Pediococcus acidilactici U318, were used asmultiple starter culture. The results showed that the growth of LAB increased after 24 hfermentation. The addition of 0.5-1.0% turmeric could enhance the growth of LAB. The additionof 1-2% turmeric suppressed the growth of Enterobacteriaceae to undetected level after 48 hfermentation. The growth of Staphylococcus aureus tended to decrease during fermentation, andthese bacteria were not detected on urutan which used turmeric of 1-2% after 96 h fermentation.At the initial of fermentation the growth of micrococci increased, and the bacteria decreasedgradually from 48 h fermentation until the end of fermentation. In general, using turmeric of 1%in urutan formulation could enhance the growth of LAB and suppress the growth of undesirablebacteria, such as the group of Enterobacteriaceae and Staph. aureus.